Ginsenoside Rg1: A bioactive therapeutic agent for diverse liver diseases - Mingyu Wu; Ke Li; Jiabin Wu; Xianyi Ding; Xiaotong Ma; Wenhong Wang; Weihua Xiao (Pharmacological Research)
Diverse liver diseases are characterised by late diagnosis and rapid progression and have become one of the major threats to human health. To delay the transition from benign tissue lesions to a substantial organ injury, scientists have gradually applied natural compounds derived from plants as a complementary therapy in the field of hepatology. Ginseng (Panax ginseng C. A. Meyer) is a tonic traditional Chinese herbal medicine, and natural products, including ginsenoside Rg1 (G-Rg1), which is a kind of 20(S)-protopanaxatriol saponin with a relatively high biological activity, can be isolated from the roots or stems of ginseng. Given these information, this review aimed to summarise and discuss the metabolic mechanisms of G-Rg1 in the regulation of diverse liver diseases and the measures to improve its bioavailability. As a kind of monomer in Chinese medicine with multitarget pharmacological effects, G-Rg1 can provide significant therapeutic benefits in the alleviation of alcoholic liver disease, nonalcoholic fatty liver disease, liver fibrosis, viral hepatitis, etc., which mainly rely on the inhibition of apoptosis, strengthening endogenous anti-inflammatory and antioxidant mechanisms, activation of immune responses and regulation of efflux transport signals, to improve pathological changes in the liver caused by lipid deposition, inflammation, oxidative stress, accumulation of hepatotoxic product, etc. However, the poor bioavailability of G-Rg1 must be overcome to improve its clinical application value. In summary, focusing on the hepatoprotective benefits of G-Rg1 will provide new insights into the development of natural Chinese medicine resources and their pharmaceutical products to target the treatment of liver diseases.